PENERAPAN TERAPI MUROTTAL AL-QUR’AN SURAT AR-RAHMAN UNTUK MENURUNKAN KECEMASAN PADA PASIEN CHF DI RUANG CVCU RSUD KARAWANG - Serly Serly; Yuli Herlina (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Congestive heart failure (congestive heart failure/CHF) is defined as a series of complex symptoms due to cessation of the heart's working processes, and structural and functional (Metra and Teerlink, 2017; PERKI, 2015). The initial cause of heart failure is chaos in the walls affecting the weakened heart muscle pumping in heart failure and proper circulation according to the body (Purbanto and Agustanti, 2015; Yancy et al., 2013). The type of research used is descriptive research with a case study approach. Case study research is research by examining a problem through a case consisting of a single unit. A single unit can mean one person, a group of people affected by the problem. The case study subjects in this case were Congestive Heart Failure patients who experienced anxiety nursing problems. From the results of the study of patients with Congestive Heart Failure with anxiety problems and after doing murottal Al-Qur'an Surah Ar-Rahman therapy for 3 days there was a change. Before the nursing intervention was carried out with murottal Al-Qur'an Surah Ar-Rahman therapy, the patient experienced anxiety problems after being intervened for 3 days, there was a change in the patient. On day 1, there was still anxiety before the application of the therapy, and after the application of the therapy, there was still anxiety. The 2nd day the anxiety was still going on before the application of anxiety therapy was still there and after the application the anxiety therapy was gone. The 3rd day the anxiety was gone.